2013
DOI: 10.1371/journal.pone.0054858
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Labor and Risk of Postpartum Hemorrhage in Low Risk Parturients

Abstract: ObjectiveLabor induction is an increasingly common procedure, even among women at low risk, although evidence to assess its risks remains sparse. Our objective was to assess the association between induction of labor and postpartum hemorrhage (PPH) in low-risk parturients, globally and according to its indications and methods.MethodPopulation-based case-control study of low-risk women who gave birth in 106 French maternity units between December 2004 and November 2006, including 4450 women with PPH, 1125 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
49
3
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 25 publications
11
49
3
4
Order By: Relevance
“…Same findings was found by Khireddine et al, that in low risk women, induction of labor, regardless of the method used, is associated with a higher risk of PPH than spontaneous labor [11]. In 2013 a metaanalysis published on Cochrane library reviewed the effect of labor augmentation by oxytocin on the duration of first stage, fetal and maternal adverse effects and on the risk of conversion to cesarean section, they found that no significant effect on reduction of maternal and fetal adverse effects, conversion to cesarean section, but the was a significant effect on shortening of first stage [12].…”
Section: Discussionsupporting
confidence: 81%
“…Same findings was found by Khireddine et al, that in low risk women, induction of labor, regardless of the method used, is associated with a higher risk of PPH than spontaneous labor [11]. In 2013 a metaanalysis published on Cochrane library reviewed the effect of labor augmentation by oxytocin on the duration of first stage, fetal and maternal adverse effects and on the risk of conversion to cesarean section, they found that no significant effect on reduction of maternal and fetal adverse effects, conversion to cesarean section, but the was a significant effect on shortening of first stage [12].…”
Section: Discussionsupporting
confidence: 81%
“…The drugs used to induce labor might have a direct effect on the uterine muscle and could act as a fatigue factor (by causing supra physiological contractions) on the myometrium muscle and thus lead to postpartum atony and possibly PPH. 16 However, in the present study the incidence of PPH after induced labor was high but not statistically significant.…”
Section: Discussioncontrasting
confidence: 79%
“…Compte tenu des faibles connaissances que nous avons en termes de dose optimale et d'effets secondaires, l'administration prophylactique ne pourrait être conseillé e que chez les patientes à haut risque d'hé morragie du post-partum, tenant compte de critè res validé s dans la litté rature (ané mie pendant la grossesse, anté cé dent d'hé morragie du post-partum, anomalie de placentation) [41][42][43].…”
Section: Discussionunclassified